Soil Inoculated with Streptomyces rochei D74 Invokes the Defense Mechanism of Helianthus annuus Against Orobanche cumana - Jiao Xi; Tengqi Xu; Zanbo Ding; Chongsen Li; Siqi Han; Ruina Liang; Yongqing Ma; Quanhong Xue; Yanbing Lin (Agriculture)
Orobanche cumana Wallr. is a root parasitic plant that causes considerable yield losses of up to 50% in sunflower Helianthus annuus plantations. The holoparasite fulfills its entire demand for water, minerals, and organic nutrients from the host’s vascular system. Agronomic practices alone are not effective in controlling this pest. This study investigated the mechanism of a verified plant growth-promoting strain, Streptomyces rochei D74, on the inhibition of the parasitism of O. cumana in a co-culture experiment. We conducted potted and sterile co-culture experiments using sunflower, O. cumana, and S. rochei D74. Our results suggest that the inoculated bacteria invoked the sunflower systemic resistance (SAR and ISR) by increasing the activity of resistance-related enzymes (SOD, POD, PPO, and PAL), the gene expression of systemic resistance marker genes (PR-1 and NPR1), ethylene synthesis genes (HACS. 1 and ACCO1), and JA synthesis genes (pin2 and lox). The expression levels of ISR marker genes (lox, HACS. 1, ACCO1, and pin2) increased by 1.66–7.91-fold in the seedling stage. Simultaneously, S. rochei D74 formed a protective layer on the sunflower root surface, preventing O. cumana from connecting to the vascular system of the sunflower roots. In addition, S. rochei D74 reduced 5DS synthesis of the strigol precursor substance, resulting in a reduction in O. cumana germination. These results demonstrated that the S. rochei D74 strain improved systemic resistance and decreased seed germination to prevent O. cumana parasitism.